2006
DOI: 10.1021/jp0557363
|View full text |Cite
|
Sign up to set email alerts
|

Well-Aligned Arrays of CuO Nanoplatelets

Abstract: This paper reports well-aligned arrays of CuO nanoplatelets synthesized through a hydrothermal route without template's assistance. The surface of well-aligned arrays of CuO nanoplatelets looks like a wall. These nanoplatelets, possessing four clear edges, are 50-80 nm in thickness, 150-250 nm in width, and 0.8-1.5 microm in length. Electron microscopic detection shows that the nanoplatelet grows along the [010] direction. The Ostwald ripening mechanism has been used to describe the growth of CuO nanoplatelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(103 citation statements)
references
References 74 publications
9
91
3
Order By: Relevance
“…37 The larger E g values of various CuO nanostructures have been reported, such as 3.48 eV for ultra-long CuO nanowires, 38 3.55 eV for CuO nanoplates, 39 and 3.02 eV for CuO nanoplatelets. 40 It has been reported that the specific sites of molecular adsorption were remarkably influenced by the band gap energy, and thus could remarkably influence the gas sensitive property. 37,38 3.2 Sensing performance using CuO thin films, the detection limit to H 2 S was higher than 100 ppb.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…37 The larger E g values of various CuO nanostructures have been reported, such as 3.48 eV for ultra-long CuO nanowires, 38 3.55 eV for CuO nanoplates, 39 and 3.02 eV for CuO nanoplatelets. 40 It has been reported that the specific sites of molecular adsorption were remarkably influenced by the band gap energy, and thus could remarkably influence the gas sensitive property. 37,38 3.2 Sensing performance using CuO thin films, the detection limit to H 2 S was higher than 100 ppb.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The band at 425 cm -1 can be assigned to the Cu-OH stretching mode of residual Cu(OH) 2 [61] which could be hidden in the tails of the diffraction patterns. The absorption peaks at around 418 cm -1 , 536 cm -1 and 590 cm -1 are due to stretching of the Cu-O bond along the [101] direction [62][63][64]. The peak at ca.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…[34] The bandgap of CuO with various morphology and particle sizes has been determined. Values such as 2.36 eV for CuO rodlike, [20] 2.43 eV for CuO spherical nanoparticles, [18] and 3.02 eV for CuO nanoplatelets [37] have been reported, all of them larger than the bulk value. Nitrogen adsorption-desorption measurements of the products were performed to determine the specific surface area of the CuO nanorods.…”
Section: Introductionmentioning
confidence: 99%